If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1y = 22 Solving 2x + -1y = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 2x + -1y + y = 22 + y Combine like terms: -1y + y = 0 2x + 0 = 22 + y 2x = 22 + y Divide each side by '2'. x = 11 + 0.5y Simplifying x = 11 + 0.5y
| 2(x+9)-15=-3 | | -3(m-6)=18 | | 3*12+4=n | | -4(m-8)-7m=-4(1+2m) | | -3/17p=-8 | | 12-3/2y=14 | | n-2=-4 | | 1.50p/10= | | 2(4w-5+w)=90 | | -5x+3(-4x-11)=137 | | 2x+6+4x-3= | | Log[5]x^2=log[5]16 | | (4.5)18(x)=126 | | (H+6)(h-2)h=672 | | 0.6x+1.18=0.8x+6.18 | | -28=3x | | (4.5)18x=126 | | 132/11=n | | 0.25w+0.17f=80000 | | (4.5)(18)x=126 | | 11x+12y-10=0 | | 2ln(x+7)=2.7 | | 7x+5+5x= | | -7=1+2 | | 4.5*18x=126 | | -7x-8x=-15 | | t/2-1=0 | | b^3*b^2=0 | | 4/7t-1/14t=t-9/2 | | (W+40)w=6000 | | .6612+4x+4x^2=0 | | 3+3s-(4s+1)-(2s+6)= |